2019
DOI: 10.1111/1365-2745.13274
|View full text |Cite
|
Sign up to set email alerts
|

A physiological model for predicting dynamics of tree stem‐wood non‐structural carbohydrates

Abstract: Non‐structural carbohydrates (NSC) are considered important in the metabolism of wood plants, and they are highly dynamic. Accurate and detailed modelling of NSC dynamics may increase the understanding of physiological processes. We constructed a physiological model that simulates NSC dynamics from photosynthesis, transpiration and growth carbon demand. With this model, we tested the hypotheses that production, allocation and storage explain tree‐ and forest‐level carbohydrates balance, and especially that cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
(87 reference statements)
0
27
0
Order By: Relevance
“…Carbohydrates produced by photosynthesis of leaves were significantly positively correlated with the lodging resistance index of the stem, which was important substances involved in metabolism, and their distribution in plants was affected by both individual development and environmental factors [70][71][72]. The previous study has found that the Nandou12 (shade-resistance variety) with high contents of cellulose, soluble sugar, sucrose, and starch could increase the lodging resistance index of stems of intercropped soybean seedling [21].…”
Section: Lodging Resistance and Carbohydrates Contentsmentioning
confidence: 99%
“…Carbohydrates produced by photosynthesis of leaves were significantly positively correlated with the lodging resistance index of the stem, which was important substances involved in metabolism, and their distribution in plants was affected by both individual development and environmental factors [70][71][72]. The previous study has found that the Nandou12 (shade-resistance variety) with high contents of cellulose, soluble sugar, sucrose, and starch could increase the lodging resistance index of stems of intercropped soybean seedling [21].…”
Section: Lodging Resistance and Carbohydrates Contentsmentioning
confidence: 99%
“…The latest version, 2.0, coupled a NSC pool for predicting NSC production (i.e., photosynthesis), allocation (i.e., biomass growth and respiration), and storage (i.e., set as an NSC slow pool; Fang et al., 2020). Adding the NSC active and slow pools allowed each component of growth (i.e., structural carbon: leaf, wood, and fine root) to be decoupled in time from instantaneous GPP and NPP.…”
Section: Methodsmentioning
confidence: 99%
“…pool and the slow pool), the climate, and the growth potential (Fang et al, 2020;Schiestl-Aalto et al, 2015):…”
Section: Ta B L E 1 Principal Model Attributes Of the Seven Tested Momentioning
confidence: 99%
See 2 more Smart Citations